The Impact of School Attendance on Child Working: Case from Indonesian School Operational Assistance - Karnia Nur Aniza (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
Educational subsidies are increasing school attendance, but the impact on the child’s working participation is vague. After running for five years, the government of Indonesia changed the regulation of Bantuan Operasional Sekolah (the BOS program or school operational assistance) to eliminate school fees for all elementary and junior secondary schools in 2009. This study intends to estimate the impact of hours of school attendance on children working using the 2009 regulation BOS program as an instrument. The estimation uses data from the fourth and fifth Indonesia Family Life Survey (IFLS) with Fuzzy Regression Discontinuity Design (FRDD) as methodology. The result presents that the children who benefited from the 2009 regulation BOS program spent more hours attending school than non-beneficiaries. However, the increase in school attendance is increasing the time allocation for income-generating and household work, supporting the idea that working and schooling are not perfectly substitutable.